2004
DOI: 10.1097/00024382-200404000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Inhibitors Improve Myocardial Dysfunction and Inflammation Induced by Endotoxin in Rats

Abstract: Excessive activation of calpains has been implicated in the pathophysiology of inflammation, trauma, and ischemia reperfusion injury. Here, we investigated the effects of calpain inhibition on myocardial dysfunction and inflammation induced by endotoxin in rats. Rats were treated i.v. with endotoxin (10 mg/kg) or endotoxin plus calpain inhibitors and were then prepared after 4 h for myocardial contractility assessment, detection of endothelium leukocyte interactions, and plasma TNF-alpha, nitrite/nitrate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 30 publications
2
42
0
2
Order By: Relevance
“…As we and others have previously reported (15,32,36), myocardial function, as represented by the maximal positive and minimal negative first derivatives of left ventricular pressure, was decreased in septic mice. The administration of calpain inhibitor III or PD-150606 markedly improved the myocardial dysfunction in septic mice (Fig.…”
Section: Myocardial Calpain Activity Was Increased In Septic Micesupporting
confidence: 72%
See 2 more Smart Citations
“…As we and others have previously reported (15,32,36), myocardial function, as represented by the maximal positive and minimal negative first derivatives of left ventricular pressure, was decreased in septic mice. The administration of calpain inhibitor III or PD-150606 markedly improved the myocardial dysfunction in septic mice (Fig.…”
Section: Myocardial Calpain Activity Was Increased In Septic Micesupporting
confidence: 72%
“…The ability of calpains to cleave cytoskeletal and myofilament proteins in vitro suggests a regulatory role for calpains in heart functions (19,24). Previous reports (15,32,36) have indicated that calpain activation is involved the process of myocardial dysfunction in sepsis. However, the molecular and cellular mechanisms that mediate the pathogenesis of calpaininduced myocardial dysfunction are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esm1 is a novel endothelial cell dysfunction marker. Septic rats showed an elevated Esm1 plasma level 4 h after LPS administration [37]. In septic patients the Esm1 blood level is related to the severity of illness and the outcome of the patient [38].…”
Section: Discussionmentioning
confidence: 96%
“…Neutrophils, however, mainly express calpain-1 and do not form focal adhesion complexes, and there are two reports that calpain inhibitors increase neutrophil motility (Lokuta et al, 2003;Katsube et al, 2008). Although it is not clear whether this latter effect was a result of decreased cell adhesion, there is a significant body of evidence showing that calpain inhibitors are effective in preventing neutrophil extravasation during experimental inflammation in animal models (Noble et al, 1998;Ikeda et al, 2002;Tissier et al, 2004;Cuzzocrea et al, 2000;Marzocco et al, 2004;Yoshifuji et al, 2005) and that calpain inhibition prevents full extension of pseudopodia during phagocytosis by neutrophils (Dewitt and Hallett, 2002) and spreading by lymphocytes (Stewart et al, 1998) and platelets (Croce et al, 1999). In our studies, calpain-inhibited cells were essentially quiescent, or sluggish even after IP 3 uncaging (e.g.…”
Section: Discussionmentioning
confidence: 99%